2000
DOI: 10.1083/jcb.148.3.579
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cis-Heterodimers of N- and R-Cadherins

Abstract: Classical cadherins form parallel cis-dimers that emanate from a single cell surface. It is thought that the cis-dimeric form is active in cell–cell adhesion, whereas cadherin monomers are likely to be inactive. Currently, cis-dimers have been shown to exist only between cadherins of the same type. Here, we show the specific formation of cis-heterodimers between N- and R-cadherins. E-cadherin cannot participate in these complexes. Cells coexpressing N- and R-cadherins show homophilic adhesion in which these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
173
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(184 citation statements)
references
References 47 publications
8
173
0
3
Order By: Relevance
“…We presume that the complexes formed in intracellular compartments are precursors to SALM complexes on the cell surface and that cis interactions between the SALMs are present at the cell surface. (14,49). The specificity of these interactions is also dependent largely on the extracellular domains of cadherins (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We presume that the complexes formed in intracellular compartments are precursors to SALM complexes on the cell surface and that cis interactions between the SALMs are present at the cell surface. (14,49). The specificity of these interactions is also dependent largely on the extracellular domains of cadherins (49).…”
Section: Discussionmentioning
confidence: 99%
“…(14,49). The specificity of these interactions is also dependent largely on the extracellular domains of cadherins (49).…”
Section: Discussionmentioning
confidence: 99%
“…The W2-independent mechanism required the absence of Ca ++ . Additionally, Shan et al (2000) found R-cadherin/ N-cadherin heterocomplexes could be coimmunoprecipitated from cells expressing both cadherin subtypes. They showed also that the R-cadherin/N-cadherin interaction appears to be real because E-cadherin, if coexpressed with R-cadherin, is not coimmunoprecipitated with R-cadherin.…”
Section: Cadherin Adhesion Structure: Cis-dimermentioning
confidence: 96%
“…Cis-dimer formation has been further investigated by immunoprecipitation experiments without first crosslinking the proteins (Chitaev and Troyanovsky 1998;Klingelhofer et al 2000;Shan et al 2000). Immunoprecipitations showed complexes of cadherins believed to represent cis-dimers isolated from cell lysates.…”
Section: Cadherin Adhesion Structure: Cis-dimermentioning
confidence: 99%
“…To gain insight into the structural basis for DN-cadherin adhesive functions, we sought to obtain structures of DN-cadherin ectodomain regions. We initially focused on ectodomain fragments containing the four predicted N-terminal EC domains in the mature protein, partly because prior structural and functional studies on vertebrate classical-and T-cadherins showed that cell adhesion is mediated through the N-terminal EC domains (8,9,(21)(22)(23). We determined crystal structures of two DN-cadherin ectodomain fragments: one comprising domains EC1'-EC3' in two crystal forms (I and II), both to 2.5 Å resolution, and the other comprising domains EC1'-EC4' to 2.7 Å resolution.…”
mentioning
confidence: 99%